2005
DOI: 10.1111/j.1745-7262.2005.00022.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel association between sperm deformity index and oxidative stress-induced DNA damage in infertile male patients

Abstract: SDI may be a useful tool in identifying potential infertile males with abnormal prevalence of oxidative stress (OS)-induced DNA damage. NADPH plays a role in ROS-mediated sperm DNA damage, which appears to be more evident in infertile patients with semen samples containing a high incidence of morphologically abnormal spermatozoa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 19 publications
2
34
0
1
Order By: Relevance
“…Infertile men with male factor or idiopathic diagnoses had significantly lower ROS-TAC scores than controls (Jedlinska et al, 2006). Besides, Said et al (2005) suggested that abnormal sperm morphology combined with elevated ROS production may serve as a useful indicator of potential damage to sperm DNA. On the other hand, spermatozoa are highly susceptible to damage by excessive concentrations of ROS due to the high content of polyunsaturated fatty acids within their plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infertile men with male factor or idiopathic diagnoses had significantly lower ROS-TAC scores than controls (Jedlinska et al, 2006). Besides, Said et al (2005) suggested that abnormal sperm morphology combined with elevated ROS production may serve as a useful indicator of potential damage to sperm DNA. On the other hand, spermatozoa are highly susceptible to damage by excessive concentrations of ROS due to the high content of polyunsaturated fatty acids within their plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, spermatozoa are highly susceptible to damage by excessive concentrations of ROS due to the high content of polyunsaturated fatty acids within their plasma membrane. The lipid peroxidation destroys the structure of lipid matrix in the membranes of spermatozoa, and it is associated with loss of motility and impairment of spermatogenesis (Said et al, 2005;Jedlinska et al, 2006). In the present study, administration of 400 and 600 mg/rat citrus extract for thirty consecutive days significantly increased sperm motility and viability in both experimental groups as compared with the control group, beside this research showed levels of TAC and SOD in both extracts groups were significantly increased and levels of MDA was decreased (p<0.05) and this results were consequential in 400 mg/kg extract (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Structurally, this is in agreement with our study results of significant interdependence between the percentages of sperm with a cytoplasmic droplet and midpiece defects on one hand and caspase activation and MMP integrity on the other. Our group has previously shown that sperm cytoplasmic droplet deformity is associated with excessive reactive oxygen species (ROS) production (Aziz et al, 2004;Said et al, 2005a). In view of their positive correlation with apoptosis and excessive ROS production, these immature spermatozoa with excessive cytoplasmic remnants could be responsible for male subfertility when present in abundance.…”
Section: Discussionmentioning
confidence: 99%
“…141 From studies of different groups, it was found that ROS hamper the integrity of plasma membrane and nuclear DNA, leading to breakage of DNA and chromatin crosslinking. 142 When the level of these breaks is high, it might lead to lowered fertility. 143 Immature, morphologically abnormal spermatozoa and seminal leukocytes are the main sources of ROS in ejaculates.…”
Section: Detection Of Oxidative Stress and Lipid Peroxidationmentioning
confidence: 99%